Effectiveness of Active Debate Method in English Speaking Skills of Students in SMAN 3 Padangsidimpuan - Nasution, Khairunnisah; Hasibuan, Apriyanti; Purba, Happy Sri Rezeki (Journal of English Teaching and Learning Issues, 2019)
This research aimed are : 1) Knowing the effectiveness of the debate method in improving students' speaking skills in learning English, 2) Knowing the differences in students' speaking skills using the debate method and without using debate method.The data was collected using test, they were pretest and postest. The result of evaluation was analyzed through quantitative. The results showed: There was a significant difference between the speaking skills of students who received speaking learning using the active debate method with students who received speaking learning without using the active debate method The difference in speaking skills is indicated by the results of the posttest t-test of the control group and the posttest of the experimental group, namely the calculation results show that the t count score is greater than the t table score (th: 2.882> tt: 1.994) at the 5% significance level and db 70. The results of the t-test showed that there were differences in the speaking skills of the control group students who received speaking learning without using the active debate method and the experimental group that received speaking learning using the active debate method.